Spin‐ and Space‐Multiplexing Metasurface for Independent Phase Controls of Quadruplex Polarization Channels. Issue 3 (30th November 2022) - Sun, Shi; Ma, Hui Feng; Gou, Yue; Zhang, Tai Yi; Wu, Liang Wei; Cui, Tie Jun
Abstract: Spin‐decoupled metasurfaces can realize independent phase controls of two orthogonally circularly polarized (CP) waves, and hence have attracted much attention in recent years. However, all previously reported metasurfaces capable of simultaneously manipulating the transmission and reflection of CP waves can only achieve two decoupled polarization conversion channels. In this work, a spin‐ and space‐multiplexing metasurface is proposed, that can achieve independent phase controls of four different CP conversion channels, including two cross‐polarized transmission channels and two co‐polarized reflection channels. The performance of the metasurface is experimentally validated by multi‐channel independent holographic imaging. The results show that four independent holograms are realized in four CP conversion channels by only using a single metasurface, which can greatly improve the information capacity of the metasurfaces and make full use of polarization and space resources. Abstract : A spin‐ and space‐multiplexing four‐channel metasurface is proposed in this paper, which can achieve independent phase control in two cross‐polarized transmission channels and two co‐polarized reflection channels to generate four independent holograms. The proposed spin‐ and space‐multiplexing metasurface can make full utilization of space and polarization resources, which may have potential applications in wireless communication or high‐capacity information storage.